Analisis Faktor-Faktor Penghambat dalam Perubahan Organisasi - Layla Nurul Sakinah; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
Organizational change is the process of moving an organization from its current state to a desired future state in order to improve its performance. However, many businesses continue to fail and refuse to adapt. The purpose of this research is to uncover the elements that hinder organizational change. The author's variable that hinders organizational change uses qualitative research methods. To describe the data in this study, various expert opinions and information from various literature sources were used. According to the findings, two elements contribute to resistance to change: the opposition caused by the business person and the failure to build an organizational culture that can support the change process. To ensure successful change, we need to integrate systems, processes, and behavior (people) approaches. Leaders act as agents of change not only while on projects, but throughout daily activities.